The expression of thymic stromal lymphopoietin in patients and animal models with eosinophilic otitis media. (4th May 2018) - Miura, Tomoya; Matsubara, Atsushi; Kudo, Naomi; Hara, Ryutaro; Takahata, Junko; Sasaki, Akira
Abstract: Objective: In the present study, we aimed to clarify the expression of thymic stromal lymphopoietin (TSLP), a key trigger of Th2-type allergic disease, in the middle ear mucosa of eosinophilic otitis media (EOM). Methods: An immunohistological study of TSLP was conducted in patients with EOM and in animal models of EOM constructed by intraperitoneal and intratympanic injection of ovalbumin for 7 and 14 days. In addition, the messenger RNA (mRNA) expression of TSLP in the middle ear mucosa of the animal models was analyzed using real-time PCR, and was compared with that of the control animals. Results: Immunoreactivities for TSLP were observed in the middle ear mucosa around the tympanic ostium of the eustachian tube of patients with EOM. In the animal model, strong immunoreactivity for TSLP was also observed in the eustachian tube epithelium, and mRNA expression of TSLP in the seven-day stimulated animals was significantly higher than that in the controls. Conclusion: The present study indicates that the presence of epithelium-derived TSLP in the eustachian tubes plays an important role in the onset of EOM.